Upaya Metode Make a Match untuk Meningkatkan Hasil Belajar Siswa Kelas VI pada Mata Pelajaran PAI di SDN 08 Tabek panjang - Raudhatul Indah; Laila Husni; Ratna Leni; Sukri Sikum (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to determine the improvement in student learning outcomes through the Make a Match method in Islamic Religious Education (PAI) and to identify obstacles in the learning process. A preliminary study at SDN 08 Tabek Panjang showed that 50% of students were still below the minimum passing grade due to monotonous and less varied learning. This study used the Classroom Action Research (CAR) method with a sample of 17 students. Data were collected through direct observation and analyzed qualitatively and quantitatively. The results showed a significant increase in student learning outcomes after the implementation of the Make a Match method. In cycle I, only 9 students passed with suboptimal average scores. However, in cycle II, the number of students who passed increased to 31 with an average score of 87. In addition, student activity in participating in learning also increased, from 53% in cycle I to 91% in cycle II. This improvement proves that the Make a Match method is effective in increasing student engagement and understanding in Islamic Education learning. With this strategy, students are more active, motivated, and able to achieve classical learning completeness. Therefore, this study is declared successful because the application of the Make a Match method is able to overcome the problem of low student learning outcomes and make learning more interesting and enjoyable.